Functional differentiation of stem cell-derived neurons from different murine backgrounds - Barth, Lydia; Sütterlin, Rosmarie; Nenniger, Markus; Vogt, Kaspar E. (Frontiers in Cellular Neuroscience, 2014)
Murine stem cell derived-neurons have been used to study a wide variety of neuropsychiatric diseases with a hereditary component, ranging from autism to Alzheimer’s. While a significant amount of data on their molecular biology has been generated, there is little data on the physiology of these cultures. Different mouse strains show clear differences in behavioural and other neurobiologically relevant readouts. We have studied the physiology of early differentiation and network formation in neuronal cultures derived from three different mouse embryonic stem cell lines. We have found largely overlapping patterns with some significant differences in the timing of the functional milestones. Neurons from R1 showed the fastest development of intrinsic excitability, while E14Tg2a and J1 were slower. This was also reflected in an earlier appearance of synaptic activity in R1 cultures, while E14Tg2a and J1 were delayed by up to two days. In conclusion, stem cells from all backgrounds could be successfully differentiated into functioning neural networks with similar developmental patterns. Differences in the timing of specific milestones, suggest that control cell lines and time-points should be carefully chosen when investigating genetic alterations that lead to subtle deficits in neuronal function.